Single-Subject Design Studies of Mindfulness Interventions for Behavior Change: A Scoping Review and Behavioral Conceptualization - Catagnus, Robyn M.; Garcia, Yors A.; Zhang, Dorothy X. (Advances in neurodevelopmental disorders, 2023)
Objectives We aimed to analyze the state of mindfulness-related single-subject design research through a behavior analytic lens. Methods Studies included empirical, quantitative, peer-reviewed single-subject design experiments training on mindfulness meditation, mindfulness-based practices, or mindfulness activities as a behavior change strategy for individuals. We excluded studies assessing effects of spillover or mindfulness only in combination with other techniques. Results Data from 28 studies included participant demographics, setting, implementor characteristics, dependent and independent variables, training techniques, and practice descriptions, and intervention relations, research methods, replicability, experimental design, reported reliability, validity, fidelity, generalization, and analyses of functional control. Some authors hypothesized the behavior change principles’ underlying outcomes. Few included treatment adherence or integrity data; behavioral repertoires were somewhat unclear. Many demonstrated functional control between intervention and behavior, but none examined contingencies related to training. Conclusions Several studies reported decreased problem behaviors or increased desirable behaviors, particularly for people with learning, behavior, or developmental differences. All authors described results somewhat behaviorally, but questions remain about repertoires of practice, underlying principles, and measurement. Cross-disciplinary practitioners can explore new procedures, clarify aspects of studies, and enhance methodology. We call for further development of a behavioral model of mindfulness interventions.